Overview of Shivering in Sectio Caesarea Patients Using Pethidine Therapy in Intraoperative with Spinal Anesthesia at Pandega Pangandaran Hospital - Anggi Rahman; Danang T. Yudono; Arni N. Rahmawati (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: Shivering is an unpleasant and frequent complication, the incidence is around 40-60% of cases after spinal anesthesia in section Caesarea patients. Small doses of 10-25 mg of pethidine are often used to treat shivering after spinal anesthesia. Objective: This therapy pethidine in section Caesarea patients who experienced shivering intraoperatively at Pandega Hospital Pangandaran. Method: This research method is descriptive quantitative with total sampling data collection technique of as many as 25 sections of Caesarea patients who experience shivering. Data were collected by observing the patient's age, duration of surgery, the onset of shivering, the onset of pethidine, and the degree of shivering. Result and Discussion: The results showed that pethidine was effective in reducing shivering reactions in 25 patients (100%), where patients who experienced shivering after 10 minutes of pethidine therapy became shivering degrees 0 and 1, Conclusions: Therefore, pethidine can be used as anti-shivering therapy. in addition to other drugs